Recurrent Midgut Bleeding due to Jejunal Angioleiomyoma - Mahir Gachabayov; Petr Mityushin (Case Reports in Surgery)
Angioleiomyoma being a type of true smooth muscle gastrointestinal tumors can lead to serious life-threatening gastrointestinal bleeding. We report a case of 21-year-old male patient with recurrent midgut bleeding. Contrast-enhanced CT revealed highly vascular small bowel neoplasm. The patient underwent laparotomy with bowel resection and recovered uneventfully. Histopathology revealed jejunal angioleiomyoma.